2022
DOI: 10.3390/ijerph19052508
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the Literature on Norovirus Disease from 1991–2021

Abstract: Norovirus (NoV) is one of the oldest recognized diseases and the leading causal pathogen for acute gastroenteritis (AGE) worldwide. Though numerous studies have been reported on NoV disease, limited research has explored the publication trends in this area. As a result, the objective of this work was to fill the void by conducting a bibliometric study in publication trends on NoV studies as well as discovering the hotspots. The Web of Science central assemblage database was hunted for publications from 1991 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 103 publications
4
44
0
Order By: Relevance
“…In addition, our study showed that the number of publications on remdesivir fluctuated during the year under investigation. This observation was related to findings in previous bibliometric analyses in the literature [ 24 , 79 ]. However, when the number of publications on remdesivir was presented for the year 2020, it was apparent that there was an overall increase in the number of publications in that year.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, our study showed that the number of publications on remdesivir fluctuated during the year under investigation. This observation was related to findings in previous bibliometric analyses in the literature [ 24 , 79 ]. However, when the number of publications on remdesivir was presented for the year 2020, it was apparent that there was an overall increase in the number of publications in that year.…”
Section: Discussionsupporting
confidence: 88%
“…The co-occurrences of author keywords are divided into two groups. The size of the nodes in the keyword-co-occurrences network depicts the degree of author-keyword co-occurrence, which represents the number of times two keywords occur together [ 24 ]. Thus, the bigger the node, the higher the relevance of the keywords.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bibliometric method is used to quantitatively analyse the research literature through database structure calculation and statistics [19]. This analysis can assess the research performance of groups and individuals [20] and identify academic characteristics of exchange and cooperation [21]. Therefore, bibliometric analysis can provide insight into previous studies and thereby directions for future [22].…”
Section: Introductionmentioning
confidence: 99%